Unlocking Tolerance in a Diversity through Hadith: : A Lesson-Learned from Manado, a City of a Thousand Churches - Muhammad Imran; Basri Mahmud (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
Tolerance among religious adherents in Indonesia as a plural state is necessary. Therefore, this current research aims at seeking religious tolerance among people in Manado, classifying and analyzing the implementation of hadith on religious tolerance in the city of a thousand churches. This research is qualitative descriptive research using the social-phenomenon approach. Primary and secondary data were collected through a literature review supported by empirical research. Empirical research data were collected through interviews and observation. Data were analyzed descriptively using an interactive model of Miles and Huberman, which covers data collection, data reduction, data display, data verification, and conclusion. This research shows that hadith related to tolerance in diversity are classified into five categories, i.e., giving and taking gifts or food to and from non-Muslims, trading interaction with non-Muslims, non-Muslim allowance praying at the mosque, respecting non-Muslims' corpses, and eating allowance with non-Muslims containers. Among those five categories, the only third category is not shown explicitly in the daily life of Manado people. It could be caused by the church's numbers quantitatively in Manado being more than the mosque numbers. The hadith implementation for tolerance indicates that the diversity of the Manado people does not always affiliate with the act of intolerance. Moreover, tolerance acts among 'different' people are commonly found in their daily life. It can be easily found during a public religious celebration, e.g., Ramadhan month, Idul Fitri, Christmas day, new year, and other religious ceremonies.